Evaluation of the value chain development program in Nigeria: Qualitative findings - Eissler, Sarah; Heckert, Jessica (International Food Policy Research Institute, 2024)
The International Fund for Agricultural Development (IFAD) and the Federal Government of Nigeria implemented the Nigeria Value Chain Development Program (VCDP) across six Nigerian states with the objective to improve farmer organizations’ collective efficacy, and alleviate poverty via improving rice and cassava production, farmers’ incomes, and value chain integration. The VCDP incorporated a gender-sensitive design to target women beneficiaries and improve empowerment by expanding access to training, opportunities, and resources. The VCDP also aimed to improve local infrastructure. This study presents qualitative findings from the VCDP impact evaluation. Four communities from two of the six treatment states were selected for this study: Niger and Anambra. Across study areas, sex disaggregated key-informant interview were conducted with 10 service providing agents (technical and capacity building), 8 farmer organization leaders, 14 producers, 13 processors, and 15 marketers. And 8 sex disaggregated FGDs were conducted with members of farmer organizations; 2 FGDs were also conducted with youth-only farmer organizations. Service providing agents found general success in delivering services to beneficiaries and benefitted themselves by working for the VCDP. Agents developed new skills that better enabled them to deliver services, and they benefitted from higher social standings as a result of their work. The VCDP was generally well received and improved target farmer organizations’ collective efficacy. These factors lead to improved rice and cassava production and processing, increasing access to necessary resources for value chain actors, and fostering cross node integration. Beneficiaries found that the different VCDP technical trainings that supported linkages to buyers were particularly useful for improving their outcomes within the value chains. Additionally, VCDP supported infrastructure development positively impacted value chain actors, particularly women, by reducing the time they spent on certain domestic chores and facilitated their ability to better participate in value chain activities. Some challenges persisted. Cultural norms restricted interaction between men and women in Niger state. Weak governance of participating farmer organizations, high levels of corruption, and security concerns that limited mobility and access to remote areas were especially challenging. Beneficiaries also noted that access to suitable financing was a significant challenge; the VCDP is rolling out a new financial linkages component to address this directly in 2020. Finally, beneficiaries were sometimes frustrated with what was perceived as unmet expectations or slow delivery of services by VCDP. In future iterations of VCDP and similar programs, it is recommended to continue strengthening the capacity building services to improve organizations’ collective efficacy, embed anti-corruption measures to ensure all intended beneficiaries have access to program resources, ensure appropriate and timely delivery of services to meet beneficiaries’ needs, and to strengthen the gender component of the program by increasing gender-sensitization trainings for beneficiaries, further targeting women beneficiaries for inclusion, and delivering context-specific solutions that enable all women beneficiaries have equal access to program support and resources.